PEMBERDAYAAN PEDAGANG LUMPIA DI PANTAI SANUR SEBAGAI KADER PENDAUR ULANG MINYAK JELANTAH DAN PELATIHAN PENJUALAN ONLINE - A.A.G. Indraningrat; M.D. Wijaya; I.A.A. Idawati (Buletin Udayana Mengabdi, 2022)
Lumpia street food vendors are commonly found at the Sanur Beach Denpasar. These lumpia street vendors regularly produce used cooking oil as the byproduct of frying lumpia. Normally, these lumpia vendors directly pour used cooking oil to soil without any further processing. Therefore, this community service activity was aimed to educate the representative lumpia street vendors to be aware of the negative impact of used cooking oil for health and environment. The representative partners were taught to recycle used cooking oil as washing soap. In addition, partners were equipped with some knowledge on digital marketing to boost lumpia selling during the COVID-19 pandemic. This community service activity was done by applying focus group discussion along with slide presentation of related topics. Evaluation of pre and post test showed increased understanding of partners to 42.5% regarding the negative impact of used cooking oil and the concept of digital marketing. Monitoring and evaluation activities that were performed for 1 months showed that these partners have already managed to recycle used cooking oil as washing soap. Furthermore, partners have frequently marketed their lumpia using social media, which evidently contribute to secure their income during the COVID-19 pandemic. Keywords: used cooking oil, lumpia vendors, soap, digital marketing